The Traditional Land Inheritance System of The Awo Community Enrekang Regency: a Maslahah Perspective - Alwi, Mujahid; Supardin, Supardin; Patimah, Patimah; Gassing, Abdul Qadir; Hamsir, Hamsir (Fakultas Syariah Institut Agama Islam Negeri Palu, 2025)
In general, there are three inheritance regulations that apply in Indonesia, namely Islamic inheritance regulations, customary inheritance regulations, and inheritance regulations governed by the state. The research focuses on: How is the practice of land inheritance in the Awo community of Baraka District? What are the obstacles in the implementation of Islamic inheritance in the customary inheritance law of the Awo community in Baraka District? And how is the Maslahah perspective on the land inheritance system in the Awo community of Baraka District? This study uses a qualitative field research method with a normative theological and ethnographic approach. The data sources are community leaders, religious leaders, and the Awo community. Data was collected through observation, interviews, and document studies. The findings of this study show that the land inheritance system in the Awo community has been maintained across generations through oral tradition. Inheritance land, known as